Discrimination in services: how service recovery efforts change with customer accent - Azab, Carol (Journal of business ethics, 2022)
Discrimination represents an important moral problem in the field of business ethics, and is often directed against minority groups. While most of the extant literature studies discrimination against employees, this paper studies discrimination against minority customers, addressing whether customers speaking English with an accent are discriminated against when contacting companies with a complaint. We draw upon the two literature streams of business ethics and service recovery to address discrimination in the service recovery process, as the recovery process after a service failure constitutes a critical incident for customers, in which discrimination would be a particularly important moral problem. The findings confirm that customers speaking with an accent are discriminated against, as employees may evaluate customers as both less credible and less competent depending on their accent. We further show that this discrimination extends to negative outcomes: service employees offer customers speaking with an accent lower compensation, and are less likely to go the extra mile for them. Having identified the existence of a discriminatory practice in the service recovery process, we further uncover both an underlying reason and a potential solution. Our results show that employees’ level of cultural intelligence helps alleviate discrimination. We conclude that companies could benefit from including cultural intelligence in the recruitment and training of their employees.